HUMOR WITHOUT BOUNDARIES? A TYPOLOGY OF GLOBALLY SPREAD HUMOR ON TWITTER - Nissenbaum, Asaf; Freud, David; Shifman, Limor (AoIR Selected Papers of Internet Research, 2020)
Our study examines user-generated global humor through an analysis of comic items spread on Twitter. By addressing the inherent conflict between the locality of humor and the globalizing digital participatory sphere, we aim to uncover the features of global user-generated humor. A long-term sample of humor keywords in multiple languages was used to locate 734 items reaching global audiences, which were analyzed quantitatively and qualitatively (a subset of 143). We found that such items focused on “the universal,” rather than a multicultural exchange. Additionally, the texts were characterized by five types of comic failures, each accompanied by some form of redemption: physical failure – slapstick acts featuring shortcomings in basic human behavior but accompanied by daring attitudes; failure in maintaining face, displaying “backstage” unattractive behavior but enjoying an aura of authenticity; failure in social relations – lacking popularity or charisma but inviting sympathy; failure in intercultural relations – misinterpreting the world and your place in it but compensating through basic human communicability; and failure to create meaning – using nonsense humor that is nevertheless appreciated through communal understanding. Our findings chart the meaning of human failure in the digital age as a balancing act: while individuals fail in fundamental aspects of life, shared laughter through social media offers collective ways for overcoming their failures. This dynamic exists in a liminal space, seeming to existing both everywhere and nowhere. By building on globally recognizable content and situations, global humor evokes empathy or identification from broad crowds without committing to specific identities.